Ultrasound assessment of articular cartilage: analysis of the frequency profile of reflected signals from naturally and artificially degraded samples. - Brown, C; Hughes, S; Crawford, R; Oloyede, A (2007)
This article investigates in vitro the hypothesis that the frequency profile of ultrasound reflections may be used to characterize degradation and osteoarthritic progression in articular cartilage, irrespective of the effects of transducer orientation. To this end, ultrasound echoes were taken in the time domain from the articular surface and osteochondral junction of normal, collagen meshwork-disrupted, proteoglycan-depleted, and osteoarthritic samples, converted to the frequency domain by fast Fourier transform and analyzed. Our results show the significant effects of specific enzymatic degradation programs on the ultrasound frequency profile of reflections from the cartilage surface and osteochondral junction, and their manifestation in the tissue surrounding a focal osteoarthritic defect. Collagen meshwork disruption was most apparent in the profile of reflections from the articular surface, while proteoglycan depletion was most clearly observed in the reflections from the osteochondral junction. The reflected signals from the osteochondral junction may further contain information about the subchondral bone. From these results we proposed that the analysis of specific frequencies of reflected ultrasound signals has the potential to differentiate normal from degraded articular cartilage-on-bone, when the angle of incidence can be controlled within a +/-1.2 degrees limit. This encourages further research into the effects of progressive artificial degradation of the cartilage matrix and subchondral bone on the spectral profile to quantify the relationship between the frequency profile and the level of specific degradation in naturally degraded joints.